EXPLORING ATTITUDES OF GEN Z TOWARDS METAVERSE IN EVENTS INDUSTRY - Lau, Jie Xi; Ch'ng, Chor Ban; Bi, XiaoYuan; Chan, Joo Han (International Journal of Sustainable Competitiveness on Tourism, 2024)
The "Metaverse" is an emerging network of 3D virtual realms that leverage technological advancements to create immersive, interconnected online environments mirroring the real world. This digital landscape has garnered significant attention, particularly from Generation Z (Gen Z), the next-generation cohort. Despite its prominence in various industries like online gaming, tourism, and hospitality, the metaverse's impact on the events industry remains relatively unexplored. This research aims to bridge this knowledge gap by investigating the variables influencing Gen Z's attitude (AT) towards the metaverse in the events industry. Specifically, it focuses on the factors of (I) perceived curiosity (PC), (II) perceived ease of use (PE), (III) social norms (SN), and (IV) perceived usefulness (PU). To accomplish this, a quantitative approach employing non-probability convenience sampling will be employed to survey 400 Gen Z individuals in Kuala Lumpur, Malaysia. Preliminary findings indicate that PC, PE, and PU significantly shape Gen Z's attitudes towards metaverse vents. However, the study reveals that the relationship between SN and Gen Z's attitudes is both insignificant and negative. This research extends the current understanding of the metaverse's implications in the events industry and contributes to the burgeoning body of knowledge in this emerging field. It offers valuable insights for event organisers, marketers, and technologists seeking to engage with Gen Z within the metaverse landscape. Ultimately, this study enhances our comprehension of the evolving dynamics between Gen Z and the metaverse within the context of event planning and execution